2020
DOI: 10.3346/jkms.2020.35.e324
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Acute Stroke in Patients with Coronavirus Disease 2019 and Challenges in Stroke Management during an Epidemic

Abstract: Coronavirus disease 2019 (COVID-19) is an ongoing pandemic infection associated with high morbidity and mortality. The Korean city of Daegu endured the first large COVID-19 outbreak outside of China. Since the report of the first confirmed case in Daegu on February 18, 2020, a total of 6,880 patients have been reported until May 29, 2020. We experienced five patients with ischemic stroke and COVID-19 during this period in four tertiary hospitals in Daegu. The D-dimer levels were high in all three patients in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 12 publications
0
15
0
6
Order By: Relevance
“…109 Furthermore, increased circulating inflammatory mediators activate coagulation cascades, promoting microcirculatory thrombi formation 110 in addition to promoting acute kidney injury, gastrointestinal inflammation, cardiovascular injury, and cerebrovascular injury. [109][110][111][112][113][114][115] Severe complications observed in COVID-19 patients include respiratory failure, myocardial injury, arrhythmias, stroke, kidney failure, coagulopathy, secondary bacterial infections, and gastrointestinal disease. [111][112][113][114][115] In the early stages of the pandemic, the primary cause of death was thought to be due to ARDS, caused by an excessive and prolonged production of proinflammatory cytokines-a cytokine stormthat caused extensive tissue damage.…”
Section: Coronavirus Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…109 Furthermore, increased circulating inflammatory mediators activate coagulation cascades, promoting microcirculatory thrombi formation 110 in addition to promoting acute kidney injury, gastrointestinal inflammation, cardiovascular injury, and cerebrovascular injury. [109][110][111][112][113][114][115] Severe complications observed in COVID-19 patients include respiratory failure, myocardial injury, arrhythmias, stroke, kidney failure, coagulopathy, secondary bacterial infections, and gastrointestinal disease. [111][112][113][114][115] In the early stages of the pandemic, the primary cause of death was thought to be due to ARDS, caused by an excessive and prolonged production of proinflammatory cytokines-a cytokine stormthat caused extensive tissue damage.…”
Section: Coronavirus Pathogenesismentioning
confidence: 99%
“…[109][110][111][112][113][114][115] Severe complications observed in COVID-19 patients include respiratory failure, myocardial injury, arrhythmias, stroke, kidney failure, coagulopathy, secondary bacterial infections, and gastrointestinal disease. [111][112][113][114][115] In the early stages of the pandemic, the primary cause of death was thought to be due to ARDS, caused by an excessive and prolonged production of proinflammatory cytokines-a cytokine stormthat caused extensive tissue damage. 6,[116][117][118] However, levels of cytokines, such as IL-1β, IL-1RA, IL-6, IL-8, IL-18, and TNF-α, in patients with severe COVID-19 have been shown to be elevated at levels expected in critically ill patients, including those with severe cases of COVID-19, and to not be different from those observed in patients with ARDS or sepsis.…”
Section: Coronavirus Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…3.3.1 Delayed stroke treatment. Fourteen studies reported that the COVID-19 pandemic caused significantly delayed treatment such as alteplase administration, thrombolysis, thrombectomy, or patients' consultation [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. One cohort study asserted that a trend toward more limited alteplase administration was recorded in patients with stroke throughout the COVID-19 pandemic than a year before the outbreak [17].…”
Section: Description Of the Impact Of Covid-19 On Patients With Stroke (Tablementioning
confidence: 99%
“…3.3.2 Thrombotic, blood and immune system complications. Thrombotic, blood and immune system complications are the most common reported sequelae in patients with stroke diagnosed with COVID-19 [17][18][19][31][32][33][34][35]. One cohort study shows that acute ischemic stroke patients diagnosed with COVID-19 developed a systemic thrombotic complication [17].…”
Section: Description Of the Impact Of Covid-19 On Patients With Stroke (Tablementioning
confidence: 99%